Best practices of handling, processing, and interpretation of small intestinal biopsies for the diagnosis and management of celiac disease: A joint consensus of Indian association of pathologists and microbiologists and Indian society of gastroenterology - Prasenjit Das; Kim Vaiphei; Anjali D Amarapurkar; Puja Sakhuja; Ritambhra Nada; Roopa Rachel Paulose; Rachana Chaturvedi; Anuradha Sekaran; Usha Kini; Archana Rastogi; Niraj Kumari; Anna Pulimood; et al. (Wolters Kluwer Medknow Publications, 2021)
The Indian Association of Pathologists and Microbiologists (IAPM) and Indian Society of Gastroenterology (ISG) decided to make a joint consensus recommendation for handling, processing, and interpretation of SI biopsies for the diagnosis and management of celiac disease (CD) recognizing the inhomogeneous practice of biopsy sampling, orientation, processing, and interpretation. A modified Delphi process was used to develop this consensus document containing a total of 42 statements and recommendations, which were generated by sharing the document draft, incorporating expert's opinion, followed by three cycles of electronic voting as well as a full-day face-to-face virtual ZOOM meeting and review of supporting literature. Of the 42 statements, 7 statements are on small intestinal (SI) biopsy in suspected patients of CD, site and the number of biopsies; 7 on handling, fixative, orientation, processing, and sectioning in pathology laboratories; 2 on histological orientation; 13 statements on histological interpretation and histological grading; 3 on the assessment of follow-up biopsies; 2 statements on gluten-free diet (GFD)-nonresponsive CD; 4 on challenges in the diagnosis of CD; 2 statements each on pathology reporting protocol and training and infrastructure in this area. The goal of this guideline document is to formulate a uniform protocol agreed upon both by the experienced pathologists and gastroenterologists to standardize the practice, improve the yield of small bowel biopsy interpretation, patients' compliance, overall management in CD, and generate unified data for patient care and research in the related field.